Citrus Fruit Pigments - Fariborz Habibi; Ali Sarkhosh; Jeongim Kim; Muhammad Shahid; Fred Gmitter; Jeffrey Brecht (EDIS)
Citrus fruits enjoy popularity among consumers due to their enjoyable flavor, health-beneficial properties, and nutritional value. The peel and flesh pigmentation of different citrus species and cultivars ranges from green, to yellow, orange, pink and red. Pigmentation is influenced by genetics, environmental conditions, and tree management. Mature fruit of edible citrus are diverse in size, flavor, and peel and flesh color. The external color of citrus fruits is one of their most important quality characteristics, but the internal pigments also play a significant role in determining their health benefits. The edible part of citrus fruits, including sweet orange, mandarin, pummelo, grapefruit, lime, and lemon, has distinct attributes and pigments.